Real-world survival outcomes with immune checkpoint inhibitors in large-cell neuroendocrine tumors of lung. Issue 2 (17th February 2021) - Dudnik, Elizabeth; Kareff, Samuel; Moskovitz, Mor; Kim, Chul; Liu, Stephen V; Lobachov, Anastasiya; Gottfried, Teodor; Urban, Damien; Zer, Alona; Rotem, Ofer; Onn, Amir; Wollner, Mira; et al.
Abstract : Background: Little is known regarding the efficacy of immune checkpoint inhibitors (ICI) in patients with advanced large-cell neuroendocrine lung carcinoma (aLCNEC). Methods: 125 consecutive patients with aLCNEC were identified in the electronic databases of 4 participating cancer centers. The patients were divided into group A (patients who received ICI, n=41) and group B (patients who did not receive ICI, n=84). Overall survival since advanced disease diagnosis (OS DX) and OS since ICI initiation (OS ICI) were captured. Results: With a median follow-up of 11.8 months (mo) (IQR 7.5–17.9) and 6.0mo (IQR 3.1–10.9), 66% and 76% of patients died in groups A and B, respectively. Median OS DX was 12.4mo (95% CI 10.7 to 23.4) and 6.0mo (95% CI 4.7 to 9.4) in groups A and B, respectively (log-rank test, p=0.02). For ICI administration, HR for OS DX was 0.59 (95% CI 0.38 to 0.93, p=0.02—unadjusted), and 0.58 (95% CI 0.34 to 0.98, p=0.04—adjusted for age, Eastern Cooperative Oncology Group (ECOG) performance status (PS), presence of liver metastases and chemotherapy administration). In a propensity score matching analysis (n=74; 37 patients in each group matched for age and ECOG PS), median OS DX was 12.5 mo (95% CI 10.6 to 25.2) and 8.4 mo (95% CI 5.4 to 16.9) in matched groups A and B, respectively (log-rank test, p=0.046). OS ICI for patients receiving ICI as monotherapy (n=36) was 11.0 mo (95% CI 6.1 to 19.4). Conclusions: With the limitations of retrospective design and small sample size, the results of this real-world cohort analysis suggest a positive impact of ICI on OS in aLCNEC.